Priesthood Satisfaction and the Challenges Priests Face: A Case Study of a Rural Diocese in the Philippines - Cornelio, Jayeel (Archīum Ateneo, 2012)
This article draws from the experience of Catholic priests based in a rural diocese in the Philippines. It will be argued that their satisfaction as diocesan priests is best understood as a religious emotion in spite of the challenges they face on a daily basis. Their challenges revolve around economic limitation, problems with their bishop and leaders, and relational isolation brought about by social and geographic distance. In spite of these challenges, priest-respondents have asserted that they are satisfied because they are still able to fulfill their vocation as priests and have an impact on the lives of their parishioners. Priesthood satisfaction in this sense is not an individual state of the mind dependent on the environment and circumstances. Instead, priesthood satisfaction can be understood as a religious emotion that allows them to remain faithful to their vocation as Catholic priests. The nuances explored in this article inform and complement the various studies on priesthood in the West.